2013
DOI: 10.1017/s1368980012005368
|View full text |Cite
|
Sign up to set email alerts
|

Relative validity of the Children's Eating Habits Questionnaire–food frequency section among young European children: the IDEFICS Study

Abstract: Objective: To compare, specifically by age group, proxy-reported food group estimates obtained from the food frequency section of the Children's Eating Habits questionnaire (CEHQ-FFQ) against the estimates of two non-consecutive 24 h dietary recalls (24-HDR). Design: Estimates of food group intakes assessed via the forty-three-food-group CEHQ-FFQ were compared with those obtained by a computerized 24-HDR. Agreement on frequencies of intakes (equal to the number of portions per recall period) between the two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
133
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(146 citation statements)
references
References 40 publications
(70 reference statements)
8
133
1
3
Order By: Relevance
“…Other authors have also reported that responses on portions and servings may differ between FFQ and recall and that this mismatch could influence correlations [26]. Other reasons cited were related to the difficulty of 24-h recalls in capturing infrequently consumed products [27,28]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have also reported that responses on portions and servings may differ between FFQ and recall and that this mismatch could influence correlations [26]. Other reasons cited were related to the difficulty of 24-h recalls in capturing infrequently consumed products [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…However, overall specificity was low except for pasta, fried potatoes, sweets and chips, and half of the items showed high NPV. The FFQ did not accurately detect non-consumers for most of the items, but the children classified as non-consumers were probably not misclassified [23,28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these forty-eight articles, sixteen articles were selected which best described the background to the project or the method used; one to three articles were typically selected per project, with the exception of the ToyBox study where articles obtained from authors were used in favour of the sourced article. Reviewing the reference lists yielded eighteen further articles in which the methods were described (29,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) .…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…Dietary history method using questionnaire X (40) 100 subjects from various participating centres were evaluated using the 3 d diet diary (two weekdays and a Sunday) in order to test the questionnaire for validity No data on SSB…”
Section: Public Health Nutritionmentioning
confidence: 99%